Intestinal helminths of capybaras, Hydrochoerus hydrochaeris, from Venezuela - Viviana Salas; Emilio A Herrera (Memorias do Instituto Oswaldo Cruz, 2004)
Quantitative parameters of intestinal helminth species and their potential relations to host characteristics in a population of capybaras (Hydrochoerus hydrochaeris) from Venezuela are reported for the first time. The intestines of 40 capybaras were collected during the 1992-annual harvest at Hato El Cedral. Six helminth species were found: 2 cestodes (Monoecocestus macrobursatum, M. hagmanni), 2 nematodes (Viannella hydrochoeri, Protozoophaga obesa), and 2 trematodes (Hippocrepis hippocrepis, Taxorchis schistocotyle). This is the first report for M. macrobursatum in Venezuela. Helminth abundance did not differ between sexes or age classes. Although patterns of distribution for all helminth species were overdispersed, the high prevalence found for all species (over 70%) and the high abundance observed for nematodes made it difficult to assess the effect that these helminths may produce on capybaras. Nevertheless, the negative associations found between the body condition of capybaras and helminth intensity for M. macrobursatum and V. hydrochoeri, might be pointing out potential host population regulatory role for these parasites which require further research.